ON THE PROPAGATION OF EQUATORIAL WAVES INTERACTING WITH A NON-UNIFORM CURRENT - Novruzov, Emil (Open Communications in Nonlinear Mathematical Physics, 2022)
We consider the propagation of equatorial waves of small amplitude, in a flow with an underlying non-uniform current. Without making the too restrictive rigid-lid approximation, by exploiting the available Hamiltonian structure of the problem, we derive the dispersion relation for the propagation of coupled long-waves: a surface wave and an internal wave. Also, we investigate the above-mentioned model of wave-current interactions in the general case with arbitrary vorticities.